1999
DOI: 10.1046/j.1365-2141.1999.01669.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin‐6 has no discriminatory role in paraproteinaemia nor a prognostic role in multiple myeloma

Abstract: We determined interleukin-6 (IL-6) levels in the serum of 212 well-defined patients with newly diagnosed paraproteinaemia and evaluated its discriminatory value and prognostic role in multiple myeloma (MM). Results were compared with serum neural cell adhesion molecule and beta-2-microglobulin, both established prognostic MM markers. Paraproteinaemia-related diagnoses were: MM (60), other haematological diseases (46), solid tumours (35), autoimmune diseases (17) and monoclonal gammopathy of unknown significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Increased serum levels of IL-6 have been documented in active MM patients [32]. However, the data are discordant due to differences in assay sensitivity [38]. By intracellular cytokine staining, a sensitive assay that directly analyses the phenotype of cytokine-producing cells, we clearly demonstrated that IL-6 production by activated T cells paralleled serum IL-6 levels and the clinical stage of MM.…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum levels of IL-6 have been documented in active MM patients [32]. However, the data are discordant due to differences in assay sensitivity [38]. By intracellular cytokine staining, a sensitive assay that directly analyses the phenotype of cytokine-producing cells, we clearly demonstrated that IL-6 production by activated T cells paralleled serum IL-6 levels and the clinical stage of MM.…”
Section: Discussionmentioning
confidence: 99%
“…8 49 73 and 4 cross-sectional studies 55 56 72 84 had recruited controls and participants free from cancer from hospital inpatients or outpatients who were likely to be less healthy than the general population. Only 10 case-control studies had used community controls, 36 64 89 and 1 cross-sectional study 34 had recruited community-living participants.…”
Section: Design and Selection Of Controlsmentioning
confidence: 99%
“…From a practical standpoint, the ability of TRAIL/Apo2L to overcome the IL-6-mediated protective effect is important since serum IL-6 levels are often elevated in MM patients [69][70][71].…”
Section: Trail/apo2l and Multiple Myelomamentioning
confidence: 99%